Investigating the Effectiveness of the Cake Application for Improving EFL Speaking Skills among Junior High School Students in Southwest Papua - Suci Sukmawati Hamdani; Hasbullah Hasbullah; Abd Rahman (Sultan Publisher, 2026)
This study investigated the specific impact of integrating Mobile-Assisted Language Learning (MALL) via the Cake application on improving the comprehensive English-speaking proficiency and behavioral classroom participation of ninth-grade students at SMP Negeri 1 Kabupaten Sorong, Southwest Papua, where instruction is traditionally textbook-bound and challenged by a complex multilingual environment. Employing a quantitative approach with a quasi-experimental pre-test and post-test non-equivalent control group design, a purposive sample of 64 students was divided into an experimental group (n = 32) and a control group (n = 32). Primary oral performance and behavioral data were analyzed using Statistical Package for the Social Sciences (SPSS), with Shapiro-Wilk (p > .05) and Levene’s test (F = 0.137, p = .712) satisfying all parametric assumptions. The independent samples t-test revealed a highly significant statistical difference in post-test oral scores, t(62) = 6.171, p < .001, with a substantial mean difference of 12.88 points favoring the experimental group (μ = 83.75 ± 6.24) over the control group (μ = 70.88 ± 5.96). Furthermore, effect size estimations yielded exceptionally high values (Cohen’s d = 1.57, Hedges’ = 1.55, and eta squared η2= 0.381), indicating that 38.1% of the variance in oral performance was directly attributable to the technological intervention. Concurrently, time-sampled observations confirmed that the application successfully lowered students' affective filters, driving a composite classroom participation rate of 82.03% (High Engagement) in the experimental class, drastically outperforming the control class at 47.66% (Low Engagement). These findings conclude that gamified, AI-assisted tools function as highly effective pedagogical scaffolds that bridge structural educational divides and enhance communicative automaticity in peripheral educational ecosystems.